Nimis poeta. Obraz grafomana w dawnej epigramatyce - Piskała, Magdalena (Śląskie Studia Polonistyczne, 2013)
The article discusses the issue of talentless writing as a topic of epigrams in both the Ancient and the Old-Polish literature. The text is an attempt to examine the emergence of the talentless writer motif in old epigrammatic literature, its subsequent persistence and its relation to the concept of poetry and the poet that prevailed in epigrammatic poetry of the era as well as in the contemporary literary theory that discussed the genre. The article reconstructs the positive model of epigrammatic poetry which emerges from epigrams about bad poets and shows how the authors relate to this model when writing about their own poetry, what shortcomings they see in their work and how they try to justify themselves in the poems addressed to their readers or critics. In order to present the problem comprehensively and answer the pertinent questions, the analysis focuses on epigrams of less-known writers such as Jan Daniecki, Albert Ines, Józef Epifani Minasowicz or Adam Łabęcki, though the leading epigrammatists of the Old-Polish period, Wespazjan Kochowski and Wacław Potocki, were also included.